2022
DOI: 10.3390/ijms232113153
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Transcription Factors to Activated Kinases in Steroidogenic and Non-Steroidogenic Cells

Abstract: Hormone-induced Leydig cell steroidogenesis requires rapid changes in gene expression in response to various hormones, cytokines, and growth factors. These proteins act by binding to their receptors on the surface of Leydig cells leading to activation of multiple intracellular signaling cascades, downstream of which are several kinases, including protein kinase A (PKA), Ca2+/calmodulin-dependent protein kinase I (CAMKI), and extracellular signal-regulated protein kinase 1 and 2 (ERK1/2). These kinases particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…In MA-10 Leydig cells, ERK1/2 has been found to functionally cooperate with STAT5B and GATA4 to activate the Star promoter [29]. The ERK1/2-GATA4 cooperation on Star is consistent with a study conducted in rat primary cardiomyocyte cells, which revealed that ERK1/2 phosphorylates GATA4 at Ser105 [66].…”
Section: Extracellular Signal-regulated Kinasesupporting
confidence: 85%
See 3 more Smart Citations
“…In MA-10 Leydig cells, ERK1/2 has been found to functionally cooperate with STAT5B and GATA4 to activate the Star promoter [29]. The ERK1/2-GATA4 cooperation on Star is consistent with a study conducted in rat primary cardiomyocyte cells, which revealed that ERK1/2 phosphorylates GATA4 at Ser105 [66].…”
Section: Extracellular Signal-regulated Kinasesupporting
confidence: 85%
“…In the mouse MA-10 Leydig cell line, active PKA translocates to the nucleus, where it phosphorylates multiple transcription factors, such as GATA4 and bZIP family members. Phosphorylation of GATA4 at Ser261 leads to increased GATA4-dependent activation of several gene promoters such as Star, Cyp17a1, aromatase, and Inha (inhibin α) [28,29]. More recently, we have shown that PKA also cooperates with COUP-TFII (NR2F2) and STAT5B to activate the Star promoter in MA-10 Leydig cells [29].…”
Section: Camp-dependent Protein Kinasementioning
confidence: 91%
See 2 more Smart Citations
“…MA-10 Leydig cells were validated by morphology and by quantifying steroidogenic output, as previously described [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. MA-10 cells were transiently transfected using polyethylenimine hydrochloride (PEI) (Sigma-Aldrich Canada, Oakville, ON, Canada), as previously described [ 61 , 63 , 64 ], or the calcium phosphate co-precipitation method, as described in [ 22 , 35 , 48 , 65 ]. Briefly, MA-10 cells were transfected 24 h after plating at a density of 100,000 cells/well, by using 0.5 μg of Insl3 promoter construct fused to the Firefly luciferase reporter gene, 20 ng of phRL-TK Renilla luciferase expression vector used as an internal control for transfection efficiency, and pSP64 as carrier DNA up to 1.5 μg/well.…”
Section: Methodsmentioning
confidence: 99%